Clinical and epidemiological characteristics of mpox among the insured population of La Libertad, 2022 - Alfaro Angulo, Marco Antonio (2024)
Objective: To describe the clinical and epidemiological characteristics of monkeypox (mpox) among the insured population of La Libertad at Seguro Social de Salud (EsSalud - Social Health Insurance System). Materials and methods: A descriptive study, whose data were collected from clinical-epidemiological records and medical records; the cases with symptoms and positive PCR results were considered. The study variables were signs and symptoms, duration of the disease, medical history, sex, age, sexual orientation and place of contact with someone with mpox. Absolute and relative frequencies and confidence intervals were calculated. Results: Mpox was developed by the insured population between July 15 and December 31, 2022, and 48 cases were reported. The clinical characteristics were fever (54.17 %), asthenia and lymphadenopathy (52.08 %) (in the inguinal [25 %], cervical [12 %] and axillary [5 %] areas), myalgia and back pain (43.75 %), sore throat (37.50 %), chills (5 %) and polymorphous and centrifugal rash (100 %). In addition, there were complications (6.25 %) and one person died (case fatality rate 6.25 %). HIV immunosuppression, history of syphilis, genital herpes and genital warts occurred in 23 (47.92 %), four (8.33%), three (6.25 %) and two (4.17 %) cases, respectively. It affected 47 men (97.92 %), including 28 homosexuals (58.33 %), 13 heterosexuals (27.08 %) and seven bisexuals (14.58 %). Ten of them had contact with someone with mpox at home (20.83 %), seven at work (14.59 %), five at a party (10.42 %) and two at a bar (4.17 %). Conclusions: Mpox occurred mainly in homosexual and bisexual men not vaccinated against human smallpox. The most common symptoms were fever, asthenia and lymphadenopathy, mainly in the inguinal area. Moreover, all cases developed polymorphous rash, the duration of the disease was 17 to 45 days, complications were exceptional, 50 % of the cases had HIV immunosuppression and the case fatality rate was 6.25 %.